Variability in flow dynamics and sedimentary facies of earthquake-triggered turbidites (seismoturbidites) in the deepest tectonic lake (Lake Hazar) along the East Anatolian Fault Zone, eastern Türkiye - Eris, Kursad Kadir; Ucarkus, Gulsen; Yakupoglu, Nurettin; Kirkan, Erdem; Yakupoglu, Cerennaz; Sabuncu, Asen; Sasmaz, Ahmet (Elsevier, 2026)
Earthquake-triggered turbidites (seismoturbidites) preserved in tectonically active lakes are valuable sedimentary archives of past seismic activity, but their facies expression and associated depositional mechanisms remain debated due to the lack of basin-wide sedimentary records that capture spatial variability across entire lake basins. Lake Hazar, T & uuml;rkiye's deepest tectonic lake along the East Anatolian Fault Zone, represents an exceptional natural laboratory for investigating the stratigraphic record of seismoturbidites. Instrumental and historical earthquake records from the surrounding region, together with the tectonically controlled physiography of the lake basin, provide favourable conditions for the formation of seismoturbidites, while the contrasting lake-floor morphology strongly influences their transport pathways, depositional processes and facies variability. In this study, seismoturbidites in Lake Hazar were examined using a series of sediment cores analysed through a multi-proxy approach combining sedimentology and geochemistry. The results provide new insight into the flow dynamics and depositional processes of seismoturbidites in a tectonic lake and highlight the complex interplay between sedimentological properties and basin physiography in controlling their formation, distribution and preservation. Four depositional facies were distinguished on the basis of their sedimentological characteristics, each reflecting distinct transport and depositional conditions within the lake basin. The coarse-grained massive facies is interpreted to record non-cohesive, sand-rich high-density flows channelized along steep lake slopes, whereas the fine-grained, clay-rich massive facies indicates deposition from more cohesive flows on low-gradient sectors of the lake basin. The most pronounced internal textural variability is recorded in graded facies, which displays normal, inverse, and mixed grading patterns, reflecting changes in source proximity, flow competence and sediment concentration during deposition. In deeper and more distal parts of the basin, the propagation and deceleration of turbidity flows promoted reworking and resuspension of slope-derived sediments, resulting in fine-grained laminated seismoturbidites. Seiche-induced water-column oscillations and associated bottom-current activity in confined deeper parts of the basin may have further contributed to the formation of coarse-grained laminated seismoturbidites. Similar unsteady-flow conditions likely produced short-term variations in transport capacity, leading to seismoturbidites characterized by internal grain-size fluctuations. Combined mu-XRF elemental compositions and total organic carbon data further indicate multiple sediment sources, derived mainly from catchment bedrock and supplemented by contributions from organic-rich unconsolidated nearshore lake sediments.
Keywords: Lake Hazar (T & Uuml;Rkiye); Seismoturbidite; Sediment Core; Grain-Size; Geochemistry